Morphological, physiological, biochemical and molecular characterization of statin-producing penicillium microfungi isolated from little-explored tropical ecosystems - Seydametova, Emine; Norazwina, Zainol (Elsevier Ltd, 2021)
As hypercholesterolemia is a primary risk factor for coronary artery disease and stroke, there is now an increasing demand for cholesterol-lowering drugs. Statins are a group of extremely successful drugs that lower the cholesterol level in the blood. Natural statins are produced by fermentation using different species of microorganisms. The overall aim of the present study was to identify statin-producing microfungi, which were isolated from different types of little-explored mangrove and oil palm plantation soils. Isolated fungal cultures were characterized on the basis of morphological, physiological, biochemical, and molecular features. Morphological variability was detected amongst the fungal isolates in regard to colony morphology, conidiophores structures, and conidia coloration. Based on their physiological properties and enzyme assays, rapid differentiation of statin-producing isolates was achieved. Further molecular characterization allowed reliable identification of the selected Penicillium microfungi up to the species level. The identified Penicillium cintrinum ESF2M, Penicillium brefeldianum ESF21P, and Penicillium janthinellum ESF26P strains have a scientific interest as novel wild-type producers of natural statins.